Employees Work-Life Balance Reviewed From Work From Home Aspect During COVID-19 Pandemic - Amanda Putri; Ali Amran (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2021)
The COVID-19 pandemic suddenly made the company inevitably has to run its operational activities in a way of work from home. The sudden change in the operational activity system can have an impact on the work-life balance of employees. In this study, the researchers wanted to know the work-life balance of the employees during the COVID-19 pandemic in terms of work from home. The research method used is a survey method with descriptive verification research type. The data used are primary data obtained from distributing the questionnaire. The results showed that work from home respectively has a positive and significant effect on the work-life balance on the employees. There are dimensions and indicators that are the highest and lowest in constructing each variable and the results of this study are expected to be used by the company to minimize and anticipate the occurrence of negative effects on work-life balance in terms of the aspects of work from home.